2013
DOI: 10.1002/jbm.a.34541
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of human osteoblasts by metal surface chemistry

Abstract: The use of metal implants in dental and orthopedic surgery is continuously expanding and highly successful. While today longevity and load-bearing capacity of the implants fulfill the expectations of the patients, acceleration of osseointegration would be of particular benefit to shorten the period of convalescence. To further clarify the options to accelerate the kinetics of osseointegration, within this study, the osteogenic properties of structurally identical surfaces with different metal coatings were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
0
9
0
1
Order By: Relevance
“…Compared with Ta, Ti cell proliferation was significantly increased after 4 days, the average cell area of Cr decreased and the proliferation ability was poor [71]. This is slightly different from the results of Hofstetter et al's in vitro study on the metal coating, which prepared 6 kinds of coatings by plasma vapor deposition (PVD), among them, Ta is more effective than Ti in cell proliferation, and similarly, Cr has the lowest surface proliferation [72]. From these results, it can be seen that the biocompatibility of Cr is poor.…”
Section: Cytological Experimentsmentioning
confidence: 58%
See 1 more Smart Citation
“…Compared with Ta, Ti cell proliferation was significantly increased after 4 days, the average cell area of Cr decreased and the proliferation ability was poor [71]. This is slightly different from the results of Hofstetter et al's in vitro study on the metal coating, which prepared 6 kinds of coatings by plasma vapor deposition (PVD), among them, Ta is more effective than Ti in cell proliferation, and similarly, Cr has the lowest surface proliferation [72]. From these results, it can be seen that the biocompatibility of Cr is poor.…”
Section: Cytological Experimentsmentioning
confidence: 58%
“…The morphological expansion, proliferation, and differentiation of cells on the surface of biomaterials are related to the expression of a series of genes and proteins after the cells are stimulated by the surface of the biomaterial. Some studies have shown that Ta has better osteogenic differentiation ability than Ti in prosthesis and implant coating, and the structural and chemical properties of the material surface have a significant influence on cell behavior, as well as the subsequent bone induction and integration [70][71][72]. The expression of ALP is a marker of osteoblast differentiation, expression analysis of bonerelated genes is also used to evaluate the osteogenic differentiation ability of cells, for example, type I collagen COL1A1 is the main component of the extracellular matrix of bone cells, and BGLAP is a marker of late osteoblast differentiation [72].…”
Section: Molecular Biology Experimentsmentioning
confidence: 99%
“…The expression of genes and proteins involved in bone growth and repair are valuable markers for demonstrating the osteoblast phenotype in vitro. Studies of variable composition and surface topographies of new developed material investigate gene expression of osteoblasts to prove their biocompatibility [33,35,37,44].…”
Section: Discussionmentioning
confidence: 99%
“…Other non-dietary elements included in current alloys, as zirconium, neodymium and "trace" rare earth elements, are supposed as low toxic; they are able to exert insignificant effects on osteoblasts. 7,34 Anyway, it is quite difficult to isolate and elucidate the specific impact of elements with small concentrations, which overlapped with the impact of magnesium and mechanical impact due to continuous corrosion and third-body wear formation on peri-implant osteogenesis in vivo.…”
Section: Discussionmentioning
confidence: 99%